Influence of gut microbial metabolites on tumor immunotherapy: mechanisms and potential natural products - Li, Dongyang; Lan, Xintian; Xu, Linyi; Zhou, Shuo; Luo, Haoming; Zhang, Xiaoying; Yu, Wenbo; Yang, Yonggang; Fang, Xiaoxue (Frontiers in Immunology, 2025)
In recent years, tumor immunotherapy has made significant breakthroughs in the treatment of malignant tumors. However, individual differences in efficacy have been observed in clinical practice. There is increasing evidence that gut microbial metabolites influence the efficacy of distal tumor immunotherapy via the gut-liver axis, the gut-brain axis and the gut-breast axis, a process that may involve modulating the expression of immune cells and cytokines in the tumor microenvironment (TME). In this review, we systematically explore the relationship between gut microbial metabolites and tumor immunotherapy, and examine the corresponding natural products and their mechanisms of action. The in-depth exploration of this research area will provide new ideas and strategies to enhance the efficacy of tumor immunotherapy and mitigate adverse effects.